HELIX MODELS AS A METHODOLOGICAL BASIS FOR ORGANISATIONAL AND ECONOMIC SUPPORT OF INNOVATIVE ENTREPRENEURSHIP - Дар’я Кравченко; Марина Салун (Економіка та суспільство)
The article substantiates the feasibility of utilising helical models (Triple, Quadruple, Quintuple Helix) as a methodological basis for innovative entrepreneurship's organisational and economic support. The text under discussion highlights the evolution of models from the triple interaction of universities, business, and the state to expanded forms involving civil society and the natural environment. The practical implementation of these strategies within the framework of European Smart Specialisation strategies and Horizon Europe, Interreg, and Erasmus+ programmes is analysed, confirming their effectiveness in transnational innovation projects. The formation of partnership structures, stakeholder interaction, and the socio-ecological dimensions of sustainable development are revealed. The proposal is for helical models to be considered a key tool in SME support policies in the context of European integration.